2007
DOI: 10.1094/pdis-91-9-1200b
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Ralstonia solanacearum Race 3 Biovar 2A Infecting Potato and Weeds in Mauritius

Abstract: In October 2005 and September 2006, two outbreaks of bacterial wilt occurred in the south and north (90 and 95 m above sea level, respectively) of Mauritius, respectively, on different potato cultivars in seed potato fields. Symptoms were reported at harvest when profuse creamy exudates were observed oozing from the eyes of tubers. The brown appearance of the vascular rings, which was accompanied by extensive maceration, suggested potato brown rot. Severe symptoms with complete rotting of vascular tissues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Unexpectedly, this study revealed that the four phylotypes of the RSSC coexist in the SWIO, representing a unique situation for such a restricted geographical area in the world. We confirmed the occurrence of phylotypes I, IIB-1, and III (formerly known as race 1/biovar 3, race 3/biovar 2, and race 1/biovar 1, respectively; Girard et al, 1993 ; Dookun et al, 2001 ; Khoodoo et al, 2007 , 2010 ; Wicker et al, 2012 ; unpublished data) and reported the presence of two strains of phylotype IV for the first time in the SWIO. Through an analysis of partial egl sequences (Fegan and Prior, 2005 ) and isolates from previous surveys (in Mayotte: Chesneau et al, submitted; and in Madagascar: Ravelomanantsoa, 2016 ; Ravelomanantsoa et al, submitted), we assigned the SWIO RSSC isolates to 14 sequevars.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Unexpectedly, this study revealed that the four phylotypes of the RSSC coexist in the SWIO, representing a unique situation for such a restricted geographical area in the world. We confirmed the occurrence of phylotypes I, IIB-1, and III (formerly known as race 1/biovar 3, race 3/biovar 2, and race 1/biovar 1, respectively; Girard et al, 1993 ; Dookun et al, 2001 ; Khoodoo et al, 2007 , 2010 ; Wicker et al, 2012 ; unpublished data) and reported the presence of two strains of phylotype IV for the first time in the SWIO. Through an analysis of partial egl sequences (Fegan and Prior, 2005 ) and isolates from previous surveys (in Mayotte: Chesneau et al, submitted; and in Madagascar: Ravelomanantsoa, 2016 ; Ravelomanantsoa et al, submitted), we assigned the SWIO RSSC isolates to 14 sequevars.…”
Section: Discussionsupporting
confidence: 79%
“…In Mauritius, we expected to collect phylotype IIB-1 isolates, since the last surveys reported potato brown rot outbreaks in several areas from 2005 to 2008 caused by race 3/biovar 2 strains that were probably introduced by latently infected potato tubers (Khoodoo et al, 2007 , 2010 ). However, we revealed the occurrence of only phylotype I isolates among a wide host range (except for the two phylotype IV isolates, surprisingly), corresponding to the BW situation before these phylotype IIB-1 outbreaks in which only race 1/biovar 3 strains were described (Dookun et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1983). The occurrence of outbreaks caused by strains belonging to Race 3 biovar 2 (R3Bv2) was first reported in Mauritius in 2007 (Khoodoo et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…R. solanacearum is a highly variable species encompassing six biovars based on biochemical properties (Hayward 1964(Hayward , 1991He et al 1983;Hayward et al 1990) and five races based on host range (Buddenhagen et al 1962;Pegg and Mofett 1971;He et al 1983). The occurrence of outbreaks caused by strains belonging to Race 3 biovar 2 (R3Bv2) was first reported in Mauritius in 2007 (Khoodoo et al 2007). Potato brown rot has been reported in 10 other countries in Africa, namely Burundi, Egypt, Ethiopia, Kenya, Libya, Reunion, Rwanda, South Africa, Tanzania and Uganda with serious economic losses (Elphinstone 2005).…”
Section: Introductionmentioning
confidence: 99%